2008
DOI: 10.1016/j.mcn.2008.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of central BDNF in mice impedes terminal differentiation of new granule neurons in the adult hippocampus

Abstract: Granule neurons generated in the adult mammalian hippocampus synaptically integrate to facilitate cognitive function and antidepressant efficacy. Here, we investigated the role of BDNF in facilitating their maturation in vivo. We found that depletion of central BDNF in mice elicited an increase in hippocampal cell proliferation without affecting cell survival or fate specification. However, new mutant neurons failed to fully mature as indicated by their lack of calbindin, reduced dendritic differentiation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
109
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(123 citation statements)
references
References 66 publications
7
109
0
1
Order By: Relevance
“…Consistent with previous reports (Sairanen et al, 2005;Chan et al, 2008), the density of BrdU-positive cells in the DG of heterozygous BDNF knock-out mice (BDNF + /À ) was significantly lower than that observed in wild-type littermate controls (BDNF + / + ; Student's t-test, t(6) ¼ 5.74, po0.01; Figure 2a). Similarly, genetic ablation of one copy of the trkb gene (TrkB + /À ) resulted in a significant reduction in the density of surviving newly born granule cells in the DG (Student's ttest, t(6) ¼ 2.44, po0.05; Figure 2b) compared with wildtype littermate controls (TrkB + / + ).…”
Section: Altered Bdnf and Trkb Expression Decrease Basal Rates Of Celsupporting
confidence: 92%
See 3 more Smart Citations
“…Consistent with previous reports (Sairanen et al, 2005;Chan et al, 2008), the density of BrdU-positive cells in the DG of heterozygous BDNF knock-out mice (BDNF + /À ) was significantly lower than that observed in wild-type littermate controls (BDNF + / + ; Student's t-test, t(6) ¼ 5.74, po0.01; Figure 2a). Similarly, genetic ablation of one copy of the trkb gene (TrkB + /À ) resulted in a significant reduction in the density of surviving newly born granule cells in the DG (Student's ttest, t(6) ¼ 2.44, po0.05; Figure 2b) compared with wildtype littermate controls (TrkB + / + ).…”
Section: Altered Bdnf and Trkb Expression Decrease Basal Rates Of Celsupporting
confidence: 92%
“…In animal models of depression, two of the potential targets of increased trophic support are through augmentation of hippocampal neurogenesis (Castren, 2004;Sahay and Hen, 2007;Schmidt and Duman, 2007) and synaptic plasticity (Manji et al, 2003;Castren, 2004;Russo-Neustadt and Chen, 2005;Wang et al, 2008), both processes are impacted by altered BDNF levels (Figurov et al, 1996;Sairanen et al, 2005;Scharfman et al, 2005;Chan et al, 2008;Donovan et al, 2008;Li et al, 2008). We found that BDNF Met/Met mice had decreased basal levels of BDNF in the hippocampus, and unlike BDNF Val/Val mice, BDNF protein levels did not increase following chronic fluoxetine treatment.…”
Section: Introductionmentioning
confidence: 67%
See 2 more Smart Citations
“…One potential mechanism may be a reduction in mitogenic factors such as FGF-2, BDNF and insulin-like growth factor 1 (IGF-1) in the epileptic hippocampus resulting in an unfavourable neurogenic environment . As neuronal differentiation rather than progenitor cell number and proliferation is predominantly affected in chronic TLE, the presence of an unfavourable hippocampal milieu due to reduction of mitogenic factors currently remains the most plausible mechanism (Altar, et al, 2004, Chan, et al, 2008.…”
Section: Potential Mechanisms Underlying Decreased Neurogenesis In Chmentioning
confidence: 99%